Phenology and growth flower of Dianthus caryophyllus L. cv. ‘MOON LIGHT’ under greenhouse - Pinzon-Sandoval, Elberth Hernando; Romero-Cuervo, Wilmar Andres; Luis-Ayala, Marco Alexander (Revista de Ciencias Agrícolas, 2021)
Carnation crop in Colombia is one of the main income generating activities in Colombian floriculture. However, the growth dynamics and its relationship with thermal time are unknown. For this reason, the objective of this research was to determine the growth and development of carnation (Dianthus caryophyllus L.) cv. ‘Moon Light’ in thermal time when grown in a greenhouse in Bogotá savanna. This research was developed based on the phenological stages and accumulation of Growing Degree Days (GDD). Fresh and dry weight accumulation is fitted to a logistic model that generated a sigmoid type curve. The carnation flower cv. 'Moon light' presented a constant accumulation of dry weight from 15.3 GDD (stage 0 rice) to 777.6 GDD (cut point). The Absolute Growth Rate (AGR) increased slowly during phase I. It presents a rapid and constant gain until reaching the cut-off point with a value of 0.035 g per GDC and an accumulation of 777.6 GDC. The Relative Growth Rate (RGR) presented a continuous decrease with an initial value of 0.0049 g g-1 per GDD in the bullet stage and a value of 0.0024 g g-1 per GDD at the cut-off point. Through the results obtained, the floriculture sector will have a technical tool within the productive projection of the carnation variety 'Moon Light' grown in a greenhouse.